'Dual' peptidyl-oligonucleotide conjugates: Role of conformational flexibility in catalytic cleavage of RNA. (January 2017) - Staroseletz, Yaroslav; Williams, Aled; Burusco, Kepa K.; Alibay, Irfan; Vlassov, Valentin V.; Zenkova, Marina A.; Bichenkova, Elena V.
Abstract: Traditional therapeutic interventions against abnormal gene expression in disease states at the level of expressed proteins are becoming increasingly difficult due to poor selectivity, off-target effects and associated toxicity. Upstream catalytic targeting of specific RNA sequences offers an alternative platform for drug discovery to achieve more potent and selective treatment through antisense interference with disease-relevant RNAs. We report a novel class of catalytic biomaterials, comprising amphipathic RNA-cleaving peptides placed between two RNA recognition motifs, here demonstrated to target the TΨC loop and 3′- acceptor stem of tRNA Phe . These unique peptidyl-oligonucleotide 'dual' conjugates (DCs) were created by phosphoramidate or thiol-maleimide conjugation chemistry of a TΨC-targeting oligonucleotide to the N -terminus of the amphipathic peptide sequence, followed by amide coupling of a 3′-acceptor stem-targeting oligonucleotide to the free C-terminal carboxylic acid functionality of the same peptide. Hybridization of the DCs bearing two spatially-separated recognition motifs with the target tRNA Phe placed the peptide adjacent to a single-stranded RNA region and promoted cleavage within the 'action radius' of the catalytic peptide. Up to 100% cleavage of the target tRNA Phe was achieved by the best candidate ( i.e. DC6) within 4 h, when conformational flexibility was introduced into the linker regions between the peptide and oligonucleotide components. This study provides the strong position for future development of highly selective RNA-targeting agents that can potentially be used for disease-selective treatment at the level of messenger, micro, and genomic viral RNA. Graphical abstract: